2014
DOI: 10.1111/jawr.12218
|View full text |Cite
|
Sign up to set email alerts
|

Reach‐Scale Comparison of Habitat and Mollusk Assemblages for Select Sites in the Clinch River with Regional Context

Abstract: Several hypotheses, including habitat degradation and variation in fluvial geomorphology, have been posed to explain extreme spatial and temporal variation in Clinch River mollusk assemblages. We examined associations between mollusk assemblage metrics (richness, abundance, recruitment) and physical habitat (geomorphology, streambed composition, fish habitat, and riparian condition) at 10 sites selected to represent the range of current assemblage condition in the Clinch River. We compared similar geomorpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 37 publications
(60 reference statements)
0
32
0
Order By: Relevance
“…(), and Ostby et al . (), the river segments addressed by these studies are not aligned with our analysis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…(), and Ostby et al . (), the river segments addressed by these studies are not aligned with our analysis.…”
Section: Discussionmentioning
confidence: 90%
“…The Clinch River of northeastern Tennessee and Virginia is a free‐flowing stream, with habitat features that are generally suitable for freshwater mussels (Ostby et al ., ). Major land uses within the watershed are forestry and agriculture (Zipper et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ostby et al . () sought to determine if the observed variations in mussel assemblages throughout the Clinch River reflect differences in physical habitat quality. This study was conducted in response to work in the southern Appalachians and elsewhere that suggests mussel assemblages are influenced by stream channel geomorphology.…”
Section: Overview Of Featured Collectionmentioning
confidence: 99%
“…None of the habitat metrics evaluated by Ostby et al . () were consistently correlated with patterns of mussel decline. However, they and other authors (Church, ; Krstolic, ) have found evidence that geomorphology may have played a more substantial role in structuring assemblages historically.…”
Section: Overview Of Featured Collectionmentioning
confidence: 99%
See 1 more Smart Citation